PERANAN LETKOL. SYAMSUL DJAFAR SEBAGAI TOKOH PEJUANG DALAM OPERASI SEROJA TAHUN 1976 - Zosluis Olan Malau; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:Lieutenant Colonel Syamsul Djafar was born on October 19, 1942, born in the village of Bandungrejo, East Java by parents named Kardjo Barso and Takjiman Marto Gami, Lieutenant Colonel Syamsul Djafar was thefifth child of eight siblings.The purpose of this research is to find out the life history of Lieutenant Colonel Syamsul Djafar, the struggle of Lieutenant Colonel Syamsul Djafar in Operation Seroja in 1976, the impact arising after Operation Seroja and the activities of Lieutenant Colonel Syamsul Djafar after serving in Operation Seroja. The method used is the historical method where data is collected through observation, interviews, documentation, and literature study. Data analysis uses historical writing method which consists of several stages, namely heuristics, verification, interpretation, and historiography. Research time starts from the submission of the proposal title until the completion of the thesis of the author. Life background of Lieutenant Colonel Syamsul Djafar who comes from underprivileged families .Lieutenant Colonel DJafar in the 1976 Seroja operation, Lieutenant Colonel. Syamsul DJafar served as an investigative officer whose function was to interrogate prisoners of war.The impact caused after the Seroja operation included two parties involved that suffered many physical and non material losses including many who died on the battlefield and in the economic and social side Decreased after finished his service in Seroja Lt. Col. Syamsul Djafar returned to his unit to continue his equally important task as the election supervisory committee or Panwas, commander of the 1/3 Pekanbaru Military Police Detachment, commander of the West Sumatra Military Police Detachment and also became chairman of the regional representative council or DPRD Pekanbaru cityKeyWords: Role, Lieutenant Colonel Syamsul Djafar, Warrior figure, Operation Seroja